Knowledge sharing framework for community of practice : single mothers - Syed Taha, Sharifah Rabeah (2010)
The purpose of this study is to identify knowledge needs by single mothers in Malaysia through the knowledge sharing concept. In addition, it also seeks to identify specific knowledge needs based on three main components such as content, services and knowledge sharing tools for single mothers community. The study also focused on how knowledge sharing is carried out among single mother, government, NGOs, children/family members, counselor and researcher. Knowledge management is a process of organizing, identifying, and sharing knowledge either tacit or explicit experience, and expertise that typically resides within individuals in an organization. Sharing of knowledge plays an important role in the development of the community. With that, it helps to improve the overall level of competency in developing a better social environment in parallel with the new generation of knowledge sharing culture for single parent’s by using the new technology. Knowledge sharing framework proposed by Aida Suzana (2009) was used to test its applicability with single mothers community in Malaysia. As a proof of knowledge sharing concept, a prototype portal was build for single mother to share their knowledge and communicate each other. Portal is one of knowledge sharing tools used to present information from diverse sources in a unified way and in the same. The study will also help to form the members towards making them become more aware on the importance of knowledge sharing culture.